Droga na Syberię polskich kobiet na przykładzie: Ewy Felińskiej, Marii Morzyckiej i Jadwigi Prendowskiej - Cedro, Wojciech (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
The defeat of the January Uprising caused the Russian repression against the polish society. One of the hardest punishments was an exiled to Siberia – the place which was known as an uncivilized land with an extremely adverse climate. Among the exiles can be find as well as women. Part of them were penalized for their politician activity against Russian administration. They frequently acted as the conspirators, couriers involved in the struggle for independence. The second group of women were, the most frequently, the wives of the exiles, however there were as well as the daughters and the mothers. The aim of the article is to present the women’s journey in Siberia according to the memories of Jadwiga Prendowska and Maria Morzycka. First of them was penalized due to her independence activities, whereas the second one was sent in Siberia as a voluntary companion of her husband. The article is concerned on the similarity and the diffrences between these two women and their experiences of the journey to exile.